'For the Protection of All the People': Æthelflæd and Her Burhs in Northwest Mercia. (3rd July 2018) - Blake, Matthew; Sargent, Andrew
ABSTRACT: The fortifications, or burhs, constructed between 910 and 915 by Æthelflæd, Lady of the Mercians, across much of the western Midlands have often been understood as part of a broader programme initiated by her brother Edward, king of the Anglo-Saxons, as part of the conquest of the Danish parts of the province of Mercia. This study seeks to understand them on their own terms, attempting to characterize their nature as built elements in the early medieval landscape, and placing them within the context of textual sources directly associated with Æthelflæd and her husband Æthelred. It is concluded that, whilst Æthelflæd's burhs undoubtedly shared features with those constructed by her brother and their father, Alfred the Great, they also formed a particular corpus of their own with shared characteristics, and were conceived with several purposes, political, social and ecclesiastical as well as military, intended to answer problems specific to Æthelflæd's Mercia.